Coenopopulations of plants that need protection in Carpathian part of Dnister River (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
A floristic structure of the forest, shrub and meadow communities of the Carpathian part of Dnister River is investigated. A list of rare and endangered (red-listed) plant species is added with showing their distribution.
Keywords: coenopopulations, communities, Dnister River, rare plant species.